Systemic peptide mediated delivery of an siRNA targeting α-syn in the CNS ameliorates the neurodegenerative process in a transgenic model of Lewy body disease - Brian Spencer; Ivy Trinh; Edward Rockenstein; Michael Mante; Jazmin Florio; Anthony Adame; Omar M.A. El-Agnaf; Changyoun Kim; Eliezer Masliah; Robert A. Rissman (Neurobiology of Disease, 2019)
Neurodegenerative disorders of the aging population are characterized by progressive accumulation of neuronal proteins such as α-synuclein (α-syn) in Parkinson's Disease (PD) and Amyloid ß (Aß) and Tau in Alzheimer's disease (AD) for which no treatments are currently available. The ability to regulate the expression at the gene transcription level would be beneficial for reducing the accumulation of these proteins or regulating expression levels of other genes in the CNS. Short interfering RNA molecules can bind specifically to target RNAs and deliver them for degradation. This approach has shown promise therapeutically in vitro and in vivo in mouse models of PD and AD and other neurological disorders; however, delivery of the siRNA to the CNS in vivo has been achieved primarily through intra-cerebral or intra-thecal injections that may be less amenable for clinical translation; therefore, alternative approaches for delivery of siRNAs to the brain is needed. Recently, we described a small peptide from the envelope protein of the rabies virus (C2-9r) that was utilized to deliver an siRNA targeting α-syn across the blood brain barrier (BBB) following intravenous injection. This approach showed reduced expression of α-syn and neuroprotection in a toxic mouse model of PD. However, since receptor-mediated delivery is potentially saturable, each allowing the delivery of a limited number of molecules, we identified an alternative peptide for the transport of nucleotides across the BBB based on the apolipoprotein B (apoB) protein targeted to the family of low-density lipoprotein receptors (LDL-R). We used an 11-amino acid sequence from the apoB protein (ApoB11) that, when coupled with a 9-amino acid arginine linker, can transport siRNAs across the BBB to neuronal and glial cells. To examine the value of this peptide mediated oligonucleotide delivery system for PD, we delivered an siRNA targeting the α-syn (siα-syn) in a transgenic mouse model of PD. We found that ApoB11 was effective (comparable to C2-9r) at mediating the delivery of siα-syn into the CNS, co-localized to neurons and glial cells and reduced levels of α-syn protein translation and accumulation. Delivery of ApoB11/siα-syn was accompanied by protection from degeneration of selected neuronal populations in the neocortex, limbic system and striato-nigral system and reduced neuro-inflammation. Taken together, these results suggest that systemic delivery of oligonucleotides targeting α-syn using ApoB11 might be an interesting alternative strategy worth considering for the experimental treatment of synucleinopathies.